Clinical outcome of transcatheter closure of patent ductus arteriosus in small children weighing 10 kg or less - Park, Young A; Kim, Nam Kyun; Park, Su-Jin; Yun, Bong Sic; Choi, Jae Young; Sul, Jun Hee (Clinical and experimental pediatrics, 2010)
Transcatheter closure has become an effective therapy in most patients with patent ductus arteriosus (PDA). However, there are difficulties in transcatheter closure of PDA in small children. We reviewed clinical outcomes of transcatheter closure of PDA in children weighing less than 10 kg in a single center. Between January 2003 and December 2009, 314 patients with PDA underwent transcatheter closure in our institute. Among them, 115 weighed less than 10 kg. All of these patients underwent transcatheter closure of PDA using either COOK Detachable Coil®, PFM Nit-Occlud®, or Amplatzer duct occluder®. A retrospective review of the treatment results and complications was performed. The mean age of patients was 9.1±5.9 months (median, 8 months), and mean weight was 7.6±1.8 kg (median, 7.8 kg). The mean diameter of PDA was 3.2±1.4 mm (median, 3 mm). Complete occlusion occurred in 113 patients (98%). One patient was sent to surgery because of a failed attempt at device closure, and another patient had a small residual shunt after device placement. The average mean length of hospital stay was 3.0±3.3 days, and mean follow-up duration was 21.0±19.6 months. There were no major complications in any of the patients. Transcatheter closure of PDA is considered safe and efficacious in infants weighing less than 10 kg. With sufficient experience and further effort, transcatheter closure of PDA can be accepted as the gold standard of treatment for this group of patients.